The Role of Educational Technology and Learning Innovation in Improving the Quality of Education - Siska Aprelyani (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Literature Review of the role of educational technology and learning innovation in improving the quality of education is a scientific article with the aim of analyzing whether the quality of education plays a role in educational technology and learning innovation. The qualitative approach method with a literature review method to explore and analyze the relationship between educational technology, learning innovation and the quality of education. The results of this article are: 1) Educational Technology plays a role in the Quality of Education; 2) Learning Innovation plays a role in the Quality of Education. In addition to these two exogenous variables that influence the endogenous variable of the Quality of Education, there are still many other factors including curriculum, facilities and infrastructure, teacher quality.